Specificity of the musical interpretation of Arnold Böcklin's paintings by Max Reger - Kirdeieva, Maiia (Ukrainian Cultural Studies, 2022)
The article analyses the interaction of arts on the example of the program work Four Tone Poems after Arnold Böcklin by Max Reger, written under the impression from the paintings by Arnold Böcklin, a Swiss symbolist painter. New perspectives were found in the study of the composer's individual style. The analysis of the composition Four Tone Poems after Arnold Böcklin (1913) gives the possibility to investigate M. Reger's views on works of fine art manifested in the specific features of the music piece as well as the role of visual impression and its place in the construction of musical images. Particular attention is paid to the analysis and use of means of musical expression. Using the cultural method for researching artist biographies, it was possible to determine the exact version of the painting Isle of the Dead by A. Böcklin, which served as a program for M. Reger on the basis of which he wrote the poem of the same name (third). This article reveals the composer's style orientation, which constitutes a synthesis of romantic emotionality with a strong reliance on constructiveness, clearness and intellectuality. The article analyzes directly opposite views on M. Reger's work and identifies the original essence of the composer's art. The study tracks the composer's connections with fine arts. An interdisciplinary approach allowed reconstructing the author's perception of the visual images of the paintings The Hermit, Playing in the Waves, Isle of the Dead and Bacchantenfest. The analysis proves that the composer chose plot motifs based on the criteria of duality, which means that each motive goes hand in hand with its antipode. M. Reger sees it as a life-death formula, which is vividly embodied in the Four Tone Poems after Arnold Böcklin, where parts one and three named the Hermit and Isle of the Dead represent death and the other two – Playing in the Waves and Bacchantenfest – is life in its vigorous manifestation.
Keywords: compositional style of M. Reger's; tone poem; A. Böcklin; programming; means of musical expression; interpretation; instrumental cycle